Simulation of a Dual-Side Polished Photonic CrystalFiber for Surface Plasmon Resonance Sensing - Marinah Othman; M. I. S. Mohammad Hilmy; M. F. Mohd Fadhir; N. Mohd Faizun Saring Cisarua; J. Jamaludin; Khairul Nabilah Zainul Ariffin; N. N. H. Saris (IEEE Photonics Society, Malaysia Chapter., 2026)
Non-Indexed Publication